Upaya Meningkatkan Kompetensi Guru SMK Negeri 4 Gowa dalam Melaksanakan Proses Pembelajaran di Kelas Melalui Program Supervisi - H Kamaruddin (Jurnal Paedagogy, 2021)
This study aims to improve the competence of teachers of SMK Negeri 4 Gowa in carrying out the learning process in the classroom through a supervision program. This research method uses action research. The subjects of this study were teachers at SMK Negeri 4 Gowa. This research instrument uses observation and documentation. While the data analysis technique used descriptive analysis. The results of this study indicate that the competence of teachers at SMK Negeri 4 Gowa in implementing the learning process in the classroom through the supervision program has increased. With an intensive supervision and guidance program, it is proven to be able to improve the professionalism of teachers in classroom learning.